PENAMBAHAN TEPUNG DAUN SISIK NAGA (Drymoglosum pilloselloides) TERHADAP KECERNAAN IN VITRO KONSENTRAT BERBAHAN PAKAN FERMENTASI - Erwin Yulianto; Andi Murlina Tasse; Rahman Rahman (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2015)
This study aims to know the effect of addition of Drymoglosum pilloseloides flour on in vitro digestibility of consentrates made from fermentation feed. The treatments consist of concentrates ware added Drymoglosum pilloseloides flour 0% (R0), 0,05% (R1), 0,1% (R2), and 0,15% (R3). Experimental design was used completely randomized design (CRD) with 4 treatments and 3 replications. This study was conducted during four weeks in Animal Science Department, of Animal Science Faculty, of Haluoleo University. The average of water content of each treatment was 15,50% ± 2,56% (R0), 16,17% ± 0,32% (R1), 17,80% ± 1,57% (R2) and 16,83% ± 1,58% (R3), ash content was 25,90% ± 0,72% (R0), 21,40% ± 0,52% (R1), 20,07% ± 0,25% (R2) and 18,50% ± 0,53% (R3), dry matter digestibility was 81,33% ± 1,00% (R0), 81,73% ± 0,49% (R1), 82,27% ± 0,91% (R2) and 81,40% ± 0,10% (R3), organic matter digestibility was 81,70% ± 1,31% (R0), 83,90% ± 1,59% (R1), 83,17% ± 0,90% (R2) and 82,50% ± 0,46% (R3). The result of analysis of variance not showed that addition of Drymoglosum pilloseloides flour 0%, 0,05%, 0,10% and 0,15% significant effect (P>0,05) on water content, dry matter digestibility and organic matter digestibility. While concentrates with addition of Drymoglosum pilloseloides flour 0%, 0,05%, 0,10% and 0,15% significant effect (P<0,05) on ash content. Dry matter and organic matter digestibility were higher than normal range that usually be given to animal. Therefore concentrates with addition of Drymoglosum pilloseloides flour no decreased dry matter and dry organic digestibilities.Key Words: Drymoglosum pilloseloides, fermented feed, dry matter digestibilityThis study aims to know the effect of addition of Drymoglosum pilloseloides flour on in vitro digestibility of consentrates made from fermentation feed. The treatments consist of concentrates ware added Drymoglosum pilloseloides flour 0% (R0), 0,05% (R1), 0,1% (R2), and 0,15% (R3). Experimental design was used completely randomized design (CRD) with 4 treatments and 3 replications. This study was conducted during four weeks in Animal Science Department, of Animal Science Faculty, of Haluoleo University. The average of water content of each treatment was 15,50% ± 2,56% (R0), 16,17% ± 0,32% (R1), 17,80% ± 1,57% (R2) and 16,83% ± 1,58% (R3), ash content was 25,90% ± 0,72% (R0), 21,40% ± 0,52% (R1), 20,07% ± 0,25% (R2) and 18,50% ± 0,53% (R3), dry matter digestibility was 81,33% ± 1,00% (R0), 81,73% ± 0,49% (R1), 82,27% ± 0,91% (R2) and 81,40% ± 0,10% (R3), organic matter digestibility was 81,70% ± 1,31% (R0), 83,90% ± 1,59% (R1), 83,17% ± 0,90% (R2) and 82,50% ± 0,46% (R3). The result of analysis of variance not showed that addition of Drymoglosum pilloseloides flour 0%, 0,05%, 0,10% and 0,15% significant effect (P>0,05) on water content, dry matter digestibility and organic matter digestibility. While concentrates with addition of Drymoglosum pilloseloides flour 0%, 0,05%, 0,10% and 0,15% significant effect (P<0,05) on ash content. Dry matter and organic matter digestibility were higher than normal range that usually be given to animal. Therefore concentrates with addition of Drymoglosum pilloseloides flour no decreased dry matter and dry organic digestibilities.Key Words: Drymoglosum pilloseloides, fermented feed, dry matter digestibility